Exceptionally high brightness and long lifetime of efficient blue OLEDs for programmable active-matrix display - Chengcheng Wu; Kai-Ning Tong; Kefei Shi; Wei He; Manli Huang; Jie Yan; Siqi Li; Zhaoyun Jin; Xin Wang; Sinyeong Jung; Jingrui Ma; Yixi Zhuang; et al. (Light: Science & Applications)
Abstract Blue phosphorescent OLEDs (Ph-OLEDs) have long faced critical challenges in efficiency, stability and brightness, which are crucial for advanced display. Herein, we introduce two novel Ir(III) emitters featuring a 3,6-di(tert-butyl)-9H-carbazolyl (tBuCz) substituted tridentate carbene pincer ligand, significantly improving efficiency and stability. The tBuCz- m -CF3 and tBuCz- p -CF3 complexes are designed to enhance steric encumbrance and minimize exciton accumulation. These innovations lead to exceptional photoluminescence quantum yields (PLQY) of 98% and an impressive decay rate constant of 7.97 × 105 s−1 in doped thin films. The Ph-OLEDs emit blue light with a peak wavelength of 485 nm and CIE coordinates of (0.175, 0.446), exhibiting a peak external quantum efficiencies (EQE) of 31.62% and brightness up to 214,255 cd m−2. Notably, they shown minimal efficiency roll-off, retaining an EQE of 27.76% at 10,000 cd m−2, and 20.58% at 100,000 cd m−2. These consistent performances across various brightness levels represent a significant milestone for blue Ph-OLED technology. The devices also exhibit impressive stability, with an operational lifetime (LT50, the time taken for luminance to decrease by 50%) reaching 1237 h at 1000 cd m−2, setting new benchmarks for blue Ph-OLEDs. To enhance the color purity, hyper-OLEDs were developed with a full width at half maximum (FWHM) of 20 nm and the CIEy of 0.233, achieving an EQEm of 29.78% and LT50 of 318 h at 1000 cd m−2. We also fabricated the active-matrix (AM) blue Hyper-OLEDs with 400 pixels per inch to demonstrate their application in AM displays.